SpyGlass-Guided Photodynamic Therapy for Unresectable Cholangiocarcinoma: A Case Report and Review of the Literature - Zhou, Jiangjiao; Xiong, Li; Liu, Wei; Liu, Chun; He, Chao; Zou, Heng; Wen, Yu; Lin, Liangwu (Frontiers in Oncology, 2022)
Endoscopic retrograde cholangiopancreatography (ERCP) and biliary stent placement are standard palliative care procedures for patients with unresectable cholangiocarcinoma. However, the bile duct mucosa cannot be observed directly during the placement of a light diffuser in photodynamic therapy (PDT) and biopsy. SpyGlass can solve the above two problems. In this paper, we report the case of a patient who presented with obstructive jaundice and underwent endobiliary stenting placement several times. However, cholangiocarcinoma hyperplasia still led to stent blockage. We applied SpyGlass to guide the accurate placement of a light diffuser and evaluated the tumor necrosis after PDT. Results revealed the good application effect of this device.